Servicio al cliente en la distribuidora Propaz de la ciudad de Babahoyo. - Rodríguez Moncada, Jackson Alexander (2022)
The present case of La Distribuidora PROPAZ, reflects that due to a series of problems that the entity presents when studying customer service. Factors such as lack of staff commitment, poor communication, unpleasant customer service, among others, call the organization into question, making its goals every day totally difficult to achieve, and turning competing companies into rivals that could alter its presence in the market. Customer Service is the main objective for the constant growth of the company, due to the fact that it attends to the complaints, suggestions and opinions of the clients. In the distributor, consumers are not satisfied with the treatment received by the employees of the place, the attitudes that these usually make customers uncomfortable, the waiting times are usually very long and the lack of knowledge of several workers makes it even more complicated the purchase process. All the information exposed in this case study was collected through the study tool that was the survey, directed both to the users and to the collaborators of the Propaz Distributor; Starting from a general analysis, the deficient existence of the service provided to the client is corroborated for different reasons that were exposed in this investigation.